Moisturising effects of water soluble chitosan based vitamin-e cream - Omar, Sarah Adila (2016)
Dry skin had been the most frequent and exacerbating dermatological problem. There are varies types of moisturisers which are commercially available and have been proven efficacious due to their good moisturising benefits towards dry skin. Vitamin E is one of them which had been used since long time as a moisturising cream. Chitosan has also been well studied for its strong moisturising properties towards dry skin problem. Thus, the present study was aimed to evaluate the significance of co-administration of HA and CS to improve hydration level of the skin by synergistic action. This study was conducted on six volunteers (n=6) in which test cream (water soluble chitosan (WSC)-based vitamin E cream was applied and evaluated compared with commercial vitamin E cream as positive control. The cosmetic effect of tested formulations was investigated by evaluating hydration level, erythema intensity, transepidermal water loss (TEWL) and the sebum contents of the skin. Resulting data revealed that WSC-based vitamin E cream showed higher increase in the hydration level, which was from 56 to 88 and sebum contents was 198 and significant reduction in the TEWL from 14.3 to 9.8 and erythema intensity from 368 to 243 compared to the positive control groups. In conclusion, we anticipate that CS based vitamin E cream can be a promising alternative therapy for the treatment of xerosis.